Sokoban: An assignment for an object-oriented and GUI programming course - Barros, João (2024)
Motivating assignments is a well-known way to promote deeper learning in programming courses. As those assignments must also be aligned with the intended learning outcomes and preferably carry some novelty, the search for adequate assignments is permanent. This poster proposes a classical 2D one-person game that provides a solid basis for discussing and applying object-oriented concepts, GUI programming, and simple patterns. It was applied in an introductory object-oriented course. Students’ feedback was highly positive, and anecdotal evidence suggests improved motivation and learning. Additionally, the game can be easily extended with some extra requirements and is amenable to different degrees of scaffolding. Hence, it can be used in more introductory or more advanced courses.